Biomechanical analysis and rehabilitation in athletes - Pastorelli, Francesca (CIC Edizioni Internazionali, 2013)
Posture is defined as the position of the body at a given point in time. Incorrect relationship among different parts of body produces an higher tension on retaining structure that causes postural problems. Posturology is fundamental to recognize the relationship between postural attitude and some pathological conditions otherwise difficult to recognize. We can use force platform, baropodometric or dynamometric platform to analyze tonic postural system and to evaluate sensitive receptors. The main injuries in athletes are caused by cumulative trauma. Rehabilitation process is divided in three phases: an acute phase, a post-acute phase and a “return to play” phase. The goal of prevention and rehabilitation is to find and remove stress and pathologic agent, to reduce the limitation of the range of motion, control pain and come back to sport.